2020
DOI: 10.1515/jpem-2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone therapy on thyroid function in isolated growth hormone deficient and short small for gestational age children: a two-year study, including on assessment of the usefulness of the thyrotropin-releasing hormone (TRH) stimulation test

Abstract: BackgroundThe relationship between growth hormone (GH)-replacement therapy and the thyroid axis in GH-deficient (GHD) children remains controversial. Furthermore, there have been few reports regarding non-GHD children. We aimed to determine the effect of GH therapy on thyroid function in GHD and non-GHD children and to assess whether thyrotropin-releasing hormone (TRH) stimulation test is helpful for the identification of central hypothyroidism before GH therapy.MethodsWe retrospectively analyzed data from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…GH treatment leads to lower serum free thyroxine (T4) levels in 14% of children born SGA in the presence of normal TSH levels, which is due an increased conversion of free T4 to biologically active free triiodothyronine (T3) ( 210 ). GH treatment does not result in thyroid dysfunction ( 210 , 211 ).…”
Section: Clinical Management Of Children Born Sgamentioning
confidence: 99%
“…GH treatment leads to lower serum free thyroxine (T4) levels in 14% of children born SGA in the presence of normal TSH levels, which is due an increased conversion of free T4 to biologically active free triiodothyronine (T3) ( 210 ). GH treatment does not result in thyroid dysfunction ( 210 , 211 ).…”
Section: Clinical Management Of Children Born Sgamentioning
confidence: 99%
“…A few studies have reported the effects of GH treatment on thyroid function in patients with a GH deficiency and hypopituitarism (17)(18)(19). GH may increase the serum FT3 level and decrease the serum FT4 level by up-regulating type 2 iodothyronine deiodinase expression (20).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, low baseline fT4 levels in children with congenital GHD are proposed as a predictor of structural pituitary lesions and diagnosis of MPHD [27]. An interesting idea was postulated recently by Ebuchi et al [29], who reported that a thyrotropin-releasing hormone (TRH) stimulation test, conducted before the initiation of growth promoting treatment, could help to identify individuals who are at risk of central hypothyroidism due to rhGH therapy and could require L-thyroxine replacement therapy. Nevertheless, this method of prediction seems to be relatively expensive and not widely available.…”
Section: Research Of Literature Datamentioning
confidence: 99%